Cardiac rehabilitation - Baniya, G B (Nepalese Heart Journal, 2000)
Heart Disease Is the leading cause of death in most of the developed world. Still malnutrition and infectious diseases are the major problem of the third world. Simultaneously with these problem, heart diseases not only of rheumatic origin, even coronary, are also increasing in the third world.